Angiogenic Factors in Cord Blood of Preterm Infants Predicts Subsequently Developing Bronchopulmonary Dysplasia - Wen-Chien Yang; Chien-Yi Chen; Hung-Chieh Chou; Wu-Shiun Hsieh; Po-Nien Tsao (Elsevier, 2015)
Bronchopulmonary dysplasia (BPD) of prematurity is associated with impaired angiogenesis. Excess soluble fms-like tyrosine kinase-1 (sFlt-1) and lower levels of vascular endothelial growth factor (VEGF) impaired alveolarization in preterm rats. Overexpression of placenta growth factor (PlGF) in mice caused airspace enlargement, which is similar to BPD pathologically. Our study aimed to clarify whether cord blood levels of these angiogenic factors were associated with the development of BPD in preterm infants. Methods: Preterm infants of gestational age (GA) <35 weeks who already had all the data of cord blood VEGF, PlGF, and sFlt-1 levels in our previous studies were enrolled. Cord blood levels of VEGF, PlGF, and sFlt-1 were collected. BPD was defined as the need for supplemental oxygen or mechanical ventilation support at the postmenstrual age of 36 weeks. We used the Mann-Whitney U test for comparison between infants with and without BPD, and multivariate analysis with logistic regression to assess the association of these molecules and the development of BPD. Results: Infants with BPD had lower GA [(27 weeks (24-34) vs. 31 weeks (28-24)], lower birth body weight [882 g (620-1232) vs. 1538 g (886-2328)], a higher incidence of respiratory distress syndrome (RDS) (58% vs. 14%), and a higher level of PlGF [21.45 pg/dL (6.03-474.01) vs. 7.43 pg/dL (0.09-23.75)] as compared with those infants without BPD. The levels of VEGF and sFlt-1 did not differ significantly between the two groups. Multivariate logistic regression revealed that lower birth body weight (p = 0.022) and higher level of PlGF (p = 0.012) were significantly correlated with the development of BPD independently. There was no significant association between the level of VEGF or sFlt-1 and the development of BPD. Conclusion: Cord blood level of PlGF, rather than VEGF or sFlt-1, was significantly increased in the BPD group. Consistent with our previous report, cord blood level of PlGF may be considered as a biomarker to predict subsequently developing BPD in preterm infants.